Custard Apple (Annona squamosa L.) Leaves: Nutritional Composition, Phytochemical Profile, and Health-Promoting Biological Activities - Kumar, Manoj (Biomolecules, 2021)
Annona squamosa L. (custard apple) belongs to the family Annonaceae and is an important tropical fruit cultivated in the West Indies, South and Central America, Ecuador, Peru, Brazil, India, Mexico, the Bahamas, Bermuda, and Egypt. Leaves of custard apple plants have been studied for their health benefits, which are attributed to a considerable diversity of phytochemicals. These compounds include phenol-based compounds, e.g., proanthocyanidins, comprising 18 different phenolic compounds, mainly alkaloids and flavonoids. Extracts from Annona squamosa leaves (ASLs) have been studied for their biological activities, including anticancer, antidiabetic, antioxidant, antimicrobial, antiobesity, lipid-lowering, and hepatoprotective functions. In the current article, we discussed the nutritional and phytochemical diversity of ASLs. Additionally, ASL extracts were discussed with respect to their biological activities, which were established by in vivo and in vitro experiments. A survey of the literature based on the phytochemical profile and health-promoting effects of ASLs showed that they can be used as potential ingredients for the development of pharmaceutical drugs and functional foods. Although there are sufficient findings available from in vitro and in vivo investigations, clinical trials are still needed to determine the exact effects of ASL extracts on human health.